ASSOCIATION OF HAEMATOLOGICAL AND RADIOLOGICAL FINDINGS WITH CLINICAL OUTCOME IN HOSPITALIZED CHILDREN 2-36 MONTHS OLD WITH SEVERE LOWER RESPIRATORY TRACT INFECTION - Waris, Rehmana; Nisar, Yasir Bin; Bhatti, Naseera (Journal of Ayub Medical College Abbottabad, 2016)
Background: Despite reduction in child mortality during last decade, lower respiratory tract infection (LRTI) remained number one killer of under-five. The current study aimed to assess the association of haematological and radiological findings with clinical outcome in hospitalized children 2-36 months old with severe LRTI. Methods: In the current cross sectional study, 581 children 2-36 months old with severe LRTI were enrolled and followed at the Children Hospital, Islamabad, between 2011 and 2014. At the time of enrolment, complete history of present illness, anthropometric measurements, blood sample and chest radiograph were obtained. The primary outcome was either early clinical response (within 72 hours) or delayed clinical response (>72 hours). Multivariable logistic regression was performed to examine the association between haematological and radiological findings with clinical outcome, adjusted for potential confounding factors. Results: Of 581 enrolled children, 292 (50.3%) children had early, and 289 (49.7%) had delayed clinical response. The multivariable logistic regression showed that leucocytosis (OR 1.79, 95% CI 1.15-2.79), neutrophilia (OR 1.91, 95% CI 1.29-2.84), radiological interstitial pneumonia (OR 2.49, 95%CI 1.70-3.64), and lobar consolidation (OR 6.00, 95%CI 2.41-14.96) were significantly associated with delayed clinical response, after adjusted for potential confounding factors. Conclusions: Delayed clinical response was significantly associated with abnormal haematological and radiological findings at the time of admission in children 2-36 months old with severe LRTI. Haematological and radiological findings at the time of presentation are useful for predicting delayed clinical response in children 2-36 months old with severe LRTI. Keywords: Lower respiratory tract infection, clinical response, radiological findings, haematological findings, Clinical severity score system